The Intertwined Roles of Oxidative Stress and Endoplasmic Reticulum Stress in Glaucoma - Daire John Hurley; Caoimhe Normile; Mustapha Irnaten; Colm O'Brien (MDPI AG, 2022)
Glaucoma is the leading cause of irreversible blindness worldwide, and the burden of the disease continues to grow as the global population ages. Currently, the only treatment option is to lower intraocular pressure. A better understanding of glaucoma pathogenesis will help us to develop novel therapeutic options. Oxidative stress has been implicated in the pathogenesis of many diseases. Oxidative stress occurs when there is an imbalance in redox homeostasis, with reactive oxygen species producing processes overcoming anti-oxidant defensive processes. Oxidative stress works in a synergistic fashion with endoplasmic reticulum stress, to drive glaucomatous damage to trabecular meshwork, retinal ganglion cells and the optic nerve head. We discuss the oxidative stress and endoplasmic reticulum stress pathways and their connections including their key intermediary, calcium. We highlight therapeutic options aimed at disrupting these pathways and discuss their potential role in glaucoma treatment.